2018
DOI: 10.1021/acsaem.8b00587
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependent Photoinduced Reversible Phase Separation in Mixed-Halide Perovskite

Abstract: Even though tandem solar cells comprised of mixed-halide perovskites CH 3 NH 3 Pb(I 1−x Br x ) 3 were expected to have much higher efficiency, the observation that they undergo photoinduced phase separation/demixing put forth a limitation to their possible utility. Herein, using temperature dependent photoluminescence studies, we show that the stated photoinduced phase separation occurs only in a narrow temperature range and above a particular bromine concentration. Our observation of the disappearance of phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 54 publications
2
52
0
Order By: Relevance
“…Figure 8a). 20,51,65 Based on the distance that the composition shifted (≈ 20 μm), Di in this region would be ≈ 10 -13 cm 2 /s, which is lower than the Di estimated in the I-rich region of a CsPbBr3-MAPbI3 heterostructure at room temperature. 49 In contrast, little change was observed in the composition region 0.…”
Section: Resultsmentioning
confidence: 73%
“…Figure 8a). 20,51,65 Based on the distance that the composition shifted (≈ 20 μm), Di in this region would be ≈ 10 -13 cm 2 /s, which is lower than the Di estimated in the I-rich region of a CsPbBr3-MAPbI3 heterostructure at room temperature. 49 In contrast, little change was observed in the composition region 0.…”
Section: Resultsmentioning
confidence: 73%
“…3 ) which has been examined repeatedly in halide segregation studies and is observed to segregate for halide ratios 0.2 < x < 1. 14,38,[50][51][52][53][54][55] Because most early reports on perovskite solar cells were based on methylammonium-lead perovskites, [56][57][58][59] bandgap tunability across the UV, visible, and near IR also initially centred around MAPb(Br x Cl (1−x) ) 3 15,60,61 and MAPb(Br x I (1−x) ) 3 . 13,14,62,63 Here, the latter Br/I perovskite is of particular interest, as it offers bandgaps near 1.7 eV, the target for efficient two-terminal tandem solar cells with silicon.…”
Section: Stoichiometric Engineeringmentioning
confidence: 99%
“…While MAPb(Br x I (1−x) ) 3 has been found to segregate for halide ratios 0.2 < x < 1, 14,38,[50][51][52][53][54][55] its neat FA and Cs counterparts exhibit comparable halide segregation only within the narrower approximate compositional ranges 0.55 < x < 0.9 14,66 and 0.4 < x < 1, 16,39,45,68 Triple-cation perovskites, with a mixture of Cs, MA, and FA incorporated onto the Asites of the perovskite structure, have proven to be the most promising to date in terms of stability against halide segregation. While halide segregation is still observed in these triple-cation materials, the timescales and photon doses required to cause significant halide ion redistribution are often much greater than those needed to cause equivalent segregation in single-or double-cation perovskites.…”
Section: A-site Cation Variationmentioning
confidence: 99%
“…Easy and cost-effective fabrication, strong absorption coefficients, long diffusion length, high charge-carrier mobilities, and apparent defect tolerance makes these devices suitable alternatives to the crystalline silicon and thin-film solar cells [4]. However, abnormal hysteresis, poor long-term stability in air and light, high lead toxicity, and surface/interface issues prevent their entry into the photovoltaic device market [4][5][6]. The key to improve PCE of hybrid perovskite solar cell is to optimize the morphology of perovskite layer as light absorption, charge transport, and carrier recombination depend on film morphology [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…However, abnormal hysteresis, poor long-term stability in air and light, high lead toxicity, and surface/interface issues prevent their entry into the photovoltaic device market [4][5][6]. The key to improve PCE of hybrid perovskite solar cell is to optimize the morphology of perovskite layer as light absorption, charge transport, and carrier recombination depend on film morphology [1][2][3][4][5][6][7][8][9]. Thus different fabrication methods like one-step spin coating, two-step sequential deposition, evaporation, vapor, and additive assisted deposition, spray pyrolysis, doctor blade method etc.…”
Section: Introductionmentioning
confidence: 99%